Oxygen Delivery and Muscle Deoxygenation during Continuous, Long- and Short-Interval Exercise - Zafeiridis, A.; Kounoupis, A.; Dipla, K.; Kyparos, A.; Nikolaidis, M. G.; Smilios, I.; Vrabas, I. S. (International Journal of Sports Medicine, 2015)
This study compared the O2 delivery (a central determinant of VO2) and muscle deoxygenation (reflecting a peripheral determinant of VO2) during intense continuous, long-interval, and short-interval exercise protocols. Twelve young men completed the 3 protocols with equal overall effort. Simultaneous and continuous recordings of central hemodynamics, muscle oxygenation/deoxygenation and VO2 were performed. Peak responses for stroke volume and peripheral resistance did not differ among protocols, whereas peak cardiac output and VO2 were higher in long-interval vs. continuous and short-interval protocols with inactive rest phases (p<0.05). The average responses for all central parameters were higher in continuous and long-interval vs. short-interval exercise (p<0.05); average VO2 and exercise-time above 80% VO2max were also higher in continuous and long-interval vs. short-interval protocol (p<0.05). Muscle de-oxygenation (↑Δdeoxyhemoglobin,↓Δoxyhemoglobin, ↓muscle O2-saturation), as well as the mismatch of O2 delivery and utilization (Δdeoxyhemoglobin/VO2) were remarkably alike among protocols. In conclusion, all 3 protocols resulted in a great activation of central and peripheral determinants of VO2. When performed with equal overall effort, the intense continuous and interval modalities reveal similarities in muscle O2-utilization response, but differences in central hemodynamic and VO2 responses. Intense continuous and long-interval protocols exert a more commanding role on the cardiovascular system and VO2 response compared to short-interval exercise with inactive rest phases.
Keywords: aerobic; endurance; interval exercise; oxygen consumption; muscle oxygenation; hemodynamic